Tuning the microstructure to improve corrosion resistance of additive manufacturing high-entropy alloy in proton exchange membrane fuel cells environment. (1st April 2023) - Cheng, Hongxu; Liu, Zhuangzhuang; Luo, Hong; Pan, Zhimin; Wang, Xuefei; Zhao, Qiancheng; Qi, Xiaohong; Li, Xiaogang
Abstract: This work tuned the microstructure of laser powder bed fusion (LPBF) CoCrFeMnNi HEAs by different heat treatment processes to improve the corrosion resistance in the simulated proton exchange membrane fuel cells (PEMFCs) environment. Research indicated that different substructures influenced the electrochemical corrosion and passive behavior of the material. The corrosion resistance was improved with increasing heat treatment temperature, which was attributed to the compositional homogenization from optimized structure, avoiding Cr depletion at grain boundaries and forming a better protective passive film. After 800 °C heat treatment, the sample showed the most stable passive film during the long-time potentiostatic polarization. Highlights: The substructure is tuned by heat treatment to improve corrosion resistance. The substructure of the LPBF CoCrFeMnNi HEA plays an important role in the protection of passive film. The corrosion mechanism of the LPBF CoCrFeMnNi HEA in the PEMFCs environment is revealed.